2022
DOI: 10.1016/j.bioactmat.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Injectable polymeric nanoparticle hydrogel system for long-term anti-inflammatory effect to treat osteoarthritis

Abstract: Treatment of osteoarthritis (OA) by administration of corticosteroids is a commonly used method in clinics using anti-inflammatory medicine. Oral administration or intra-articular injection of corticosteroids can reduce the pain and progress of cartilage degeneration, but they are usually insufficient to show local and long-term anti-inflammatory effects because of their fast clearance in the body. In this study, we suggest an injectable anti-OA drug depot system for sustained drug release that provides long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…Four articles out of nine (44%) used chitosan hydrogels [ 32 , 34 , 35 , 36 ], whereas the remaining 56% used polymeric and copolymeric matrices [ 31 , 37 , 38 , 39 , 40 ]. The data were extracted and are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Four articles out of nine (44%) used chitosan hydrogels [ 32 , 34 , 35 , 36 ], whereas the remaining 56% used polymeric and copolymeric matrices [ 31 , 37 , 38 , 39 , 40 ]. The data were extracted and are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“… Amphiphilic poly (organophophazene) TCA Slow release In vitro & vivo Rats The in vitro release study showed sustained TCA release for six weeks; The hydrogel was completely degraded in rats for 42 days; Compared with the direct injection of triamcinolone acetonide solution group, the hydrogel group had significant anti-OA effect and could effectively prevent the loss of cartilage tissue. [ 84 ] HA-VS/SH-2-PEG - Viscoelasticity In vitro & vivo Rabbits; Chondrocytes Through the experiments of implanting cells in the hydrogels and injecting the hydrogels into the joints of healthy animals, it is proved that the hydrogels had good biocompatibility; The rabbit OA joint injected with viscoelastic hydrogels had better gross morphology and Mankin score. [ 184 ] GG/PVA - Viscoelasticity In vitro NIH3T3 mouse fibroblasts; Human chondrocytes No cytotoxicity [ 186 ] PNIPAM; HA Diclofenac sodium Slow and controlled release In vitro & vivo Chondrocytes; Rats Diclofenac sodium was released continuously for up to 9 days; Hydrogels particles protected the cells against the H 2 O 2 -induced chondrocytes degeneration and prevented the H 2 O 2 -caused cartilage marker protein decrease; Hydrogels particles prevented the decreased expression of collagen II and aggrecan.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Temperature-sensitive hydrogels have always been favored because they are easier to load with drugs or cells and possess more convenient in situ formation properties than other hydrogels. 66 , 67 Thermosensitive hydrogels, such as chitosan with β-glycerol phosphate, 72 glycol chitosan, 73 PEG-grafted polyalanine or poly(lactide-co-glycolide), 74–76 poly(N-isopropylacrylamide-co-acrylic acid) (p(NIPAAm-AA)), 77 , 78 poly(ethyleneglycol)-(p(HPMAm-lac)-PEG), 79 poloxamers, 80 poly(d,l-lactide)-poly(ethylene glycol)-poly(d,l-lactide) (PLEL), 81 , 82 hyaluronic acid-chitosan-poly(N-isopropylacrylamide), 83 and amphiphilic poly(organophosphazene), 84 have been increasingly applied in the treatment of OA. A previous study demonstrated that temperature-sensitive PNIPAM (poly(N-isopropylacrylamide)) hydrogels 85 could regulate drug release according to the joint temperature.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Third, implanted substitutes that can easily integrate into the host native tissues with immunocompatibility and biocompatibility. During the past decade, we have witnessed advanced progress in the field of cartilage TE, embodied by the following changes: (i) sufficient seed cell selection for applications (mesenchymal stem cells, induced pluripotent stem cells) [ [6] , [7] , [8] ]; (ii) precise patterning of biomaterials and novel biomaterials with advanced chemistries (more efficient and versatile biomaterial conjugations) [ 1 , 9 , 10 ]; (iii) active modulation of cellular biological functions and behaviors via structure and properties (e.g., stiffness, viscoelasticity, porosity and degradability) of biomaterials [ [11] , [12] , [13] ]; (iv) combination of biological drugs and factors are combined to improve bioavailability and bioactivity [ [14] , [15] , [16] ]; (v) rapid development of biofabrication technologies including programmed self-assembly and three-dimensional (3D) bioprinting [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%